Analisis Kinerja Keuangan Daerah Kabupaten/Kota di Provinsi Kalimantan Selatan Tahun Anggaran 2013-2017 - Sahara, Gabby Febryanti; Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The aim research (1) to know local financial performance with ratio of fiscaldecentralization degree, local financial independent, effectiveness of PAD, local financeefficiencey and growth PAD regencies/municipalities in South Borneo province 2013-2017,(2) to know business sector which contributed in PDRB. Technical analysis data is descriptifanalysis. The result research showed : by average fiscal decentralization degree ratio 9regencies still very less and 4 regencies/cities less, 7 regencies low, average local financialindependence 4 regencies still very low, 7 regencies low and 2 municipalities enoughindependence, average effectivene PAD ratio almost all of regencies/municipalities veryeffective except Banjarmasin municipality are effective, average local financial efficiencyratio 9 regencies/municipalities less effecient and 2 regencies enough efficient, whileBanjarbaru municipalities inefficient, growth PAD ratio is positive.